Konflik Hukum, Agama, dan Pancasila dalam Kasus Perkawinan Beda Agama di Indonesia: Conflicts between Law, Religion and Pancasila in the Case of Interfaith Marriages in Indonesia - Ahmad Muhammad Mustain Nasoha; Mutiara Hayatunnufus; Devinta Syahwa Novalinda; Yuli Agita Sari (DIRASAH: Jurnal Kajian Islam, 2024)
Interfaith marriage from an Islamic perspective is a complex topic that often sparks various debates among scholars and in social practice. In Islamic teachings, marriage is a sacred institution strictly regulated by Sharia law. Generally, in Islam, marriage between a Muslim and a non-Muslim (in this case, a non-Muslim who is not from the People of the Book, such as Christians and Jews) is considered invalid. This study aims to identify the discrepancy between the Marriage Law, which requires religious uniformity in marriage, and the principle of religious freedom as outlined in the first principle of Pancasila. Additionally, the study seeks to explore the legal and social impacts of this conflict on interfaith couples and society at large, as well as to propose inclusive, Pancasila-oriented solutions. This study uses a qualitative method with a case study approach to analyze the legal and Pancasila-related conflicts in cases of interfaith marriage in Indonesia. The results show that the conflict between marriage law and Pancasila values in interfaith marriage cases in Indonesia reflects a misalignment between existing legal provisions and the principle of religious freedom. This conflict has significant legal and social impacts on interfaith couples and society. Proposed solutions include regulatory revisions, education on religious tolerance, mediation, and strengthened human rights protections. It is hoped that this comprehensive and inclusive approach will help create a legal system that respects religious freedom and aligns with Pancasila values.